2013
DOI: 10.1002/adem.201300132
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Thermal Conductivity of Amorphous Al2O3 Thin Films Grown by Low Temperature ALD

Abstract: grown by atomic layer deposition could be proposed as a nonactive layer for back end processes in view of the integration of scaled phase change memory devices. In this paper we report on thermal characterization from 50 to 600°C of amorphous Al 2 O 3 thin films grown on thermally oxidized silicon substrate at a temperature of 100°C and capped with a 30 nm thick Pt layer. The effects of low temperature deposition and of a post-deposition rapid thermal annealing process (RTP) on the thermal properties of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 24 publications
3
32
0
1
Order By: Relevance
“…Measured thermal conductivities shown in Figure a for both the Al/Al 2 O 3 /C and Al/Al 2 O 3 /Si systems indicate that the data can be separated into two classes: at temperatures above 140 K, data fall approximately midway between measurements made by Lee et al and agree reasonably with each other. The obtained data also compare well with measurements on amorphous alumina produced by anodization, as well as other data on ALD deposited thin films extrapolated to lower temperature below 140 K, values start to vary substantially.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Measured thermal conductivities shown in Figure a for both the Al/Al 2 O 3 /C and Al/Al 2 O 3 /Si systems indicate that the data can be separated into two classes: at temperatures above 140 K, data fall approximately midway between measurements made by Lee et al and agree reasonably with each other. The obtained data also compare well with measurements on amorphous alumina produced by anodization, as well as other data on ALD deposited thin films extrapolated to lower temperature below 140 K, values start to vary substantially.…”
Section: Discussionsupporting
confidence: 86%
“…It is further successfully used to encapsulate organic electronic devices and is expected to help improve the lifetime of Li‐ion batteries . While much effort has been put into describing its electric, mechanical, chemical, and diffusion properties of ALD alumina, only little effort has been made to characterize its thermal properties . This knowledge could be relevant because the miniaturization of microelectronics increases significantly the criticality of thermal management.…”
Section: Introductionmentioning
confidence: 99%
“…It has therefore received a lot of attention, and its thermal properties are relatively well known. Some research groups have studied the thermal conductivity of Al 2 O 3 amorphous thin films [8][9][10][11], but the evaluation of their interfacial thermal resistances is still very incomplete [12]. Al 2 O 3 amorphous thin films are promising, since they can reduce electronic recombination losses in solar cells by the passivation of silicon surfaces, thus enabling higher efficiency [13].…”
Section: Introductionmentioning
confidence: 99%
“…We used a thermal boundary resistance of 2.8 10 -8 m 2 K W -1 for mox . 7 Although an experimental determination of the thermal boundary resistance across the Al2O3/GaN film interface is not available, we estimated oxg ≈ 1 10 -8 m 2 KW -1 based on measurements across amorphous dielectric/Si interfaces, 8 since GaN and Si have similar Debye temperatures. 9 The thermal resistance of the alumina layer can be estimated as ox = ox /( ox H ) , where ox is the temperature dependent thermal conductivity of the alumina layer.…”
Section: Thermal Conductivity Extraction Procedurementioning
confidence: 92%
“…[2][3][4] Momentum transfer from non-equilibrium phonons to charge carriers, known as phonon drag (PD), produces a Seebeck coefficient ( ph ) that adds to the Seebeck coefficient from the thermal diffusion of charge carriers ( d ). Despite the potential gains in TE efficiency, understanding the contribution of PD to the overall Seebeck coefficient has not received much consideration, largely due to early work which suggested that: (1) ph is only significant at low temperatures (T ≤ 50 K), where the TE power conversion efficiency ( ) is low; 5 (2) ph is small relative to d for degenerate semiconductors, 6,7 which are the most common TE materials due to their larger ; and (3) an increase in ph coincides with a corresponding increase the thermal conductivity ( ), [8][9][10] and thus has little benefit for power generation, because ∝ 2 / .…”
mentioning
confidence: 99%